Tractor fuel consumption in different agricultural tasks : database - López Gómez, Jesús Antonio; Loon, Jelle J. van (EiA, 2023)
In order to make sound recommendations in the face of climate change, and related low-emission farming solutions, a detailed database on fuel consumption has been started through the activity of the present report. This database will provide oversight to fuel consumption, based on tractor horsepower, attach ancillary equipment and field operation duration, and will provide base line data for fuel consumption modelling, to support climate change mitigation recommendations. For this, fuel gauge sensors were installed on two four-wheel tractors to monitor fuel usage during field operation with specific ancillary equipment, and an Excel file was generated to capture the starting values. This database includes the following parameters: tractor used, agricultural activity performed, crop, implement used, fuel consumption, time of the activity performed and location. The database will be expanded during the next year, to include two-wheel tractors and a wider variety of ancillary equipment and different field conditions.